2019
DOI: 10.2196/12216
|View full text |Cite
|
Sign up to set email alerts
|

An Interactive Website for Whiplash Management (My Whiplash Navigator): Process Evaluation of Design and Implementation

Abstract: Background Whiplash is a health and economic burden worldwide. Contributing to this burden is poor guideline adherence and variable management by health care professionals (HCPs). Web-based tools that facilitate clinical pathways of care are an innovative solution to improve management. Objective The study aimed to develop, implement, and evaluate a Web-based tool to support whiplash management following a robust process. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
(58 reference statements)
2
5
0
Order By: Relevance
“…Our findings demonstrate that the informational meetings were the most successful part of the implementation, because they created an awareness of the guidelines' existence and their potential to make good decisions with respect to examinations, and to confirm that GPs and radiologists' practice was mostly correct. This is in accordance with the literature, in which informational meetings have been seen to have great potential for change in guideline adherence [29][30][31]. Studies have reported increases in guideline adherence between 9 and 82% when applying informational meetings in different forms [11,12,29,31,32].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our findings demonstrate that the informational meetings were the most successful part of the implementation, because they created an awareness of the guidelines' existence and their potential to make good decisions with respect to examinations, and to confirm that GPs and radiologists' practice was mostly correct. This is in accordance with the literature, in which informational meetings have been seen to have great potential for change in guideline adherence [29][30][31]. Studies have reported increases in guideline adherence between 9 and 82% when applying informational meetings in different forms [11,12,29,31,32].…”
Section: Discussionsupporting
confidence: 89%
“…This is in accordance with the literature, in which informational meetings have been seen to have great potential for change in guideline adherence [29][30][31]. Studies have reported increases in guideline adherence between 9 and 82% when applying informational meetings in different forms [11,12,29,31,32]. The participants were also mostly happy with the contents of the informational meetings, which may also have contributed to the experience that this was the most successful part of the implementation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Care typically involves interventions targeted to identified risk factors, comprising active approaches of exercise within a psychologically informed cognitive behavioural framework. Based on pilot feasibility studies,32 53 this pathway was used when the participant’s presentation is more complex or when the primary HCP is less confident in management. Example scenarios are when participants have widespread pain sensitivity, dominant psychosocial factors, or when complex differential diagnosis is needed (eg, neck pain, headache, dizziness).…”
Section: Methods and Analysismentioning
confidence: 99%
“…Patients with a favourable prognosis should do well with care delivered by a primary healthcare professional (HCP), supported by high quality and credible self-management information resources 24 28 32 33. One of the barriers for implementation is the volume of options of internet-based resources, many of which have low credibility standards and contain inaccurate information 34.…”
Section: Introductionmentioning
confidence: 99%